Modified cellulose and preparation method thereof, negative electrode material and lithium ion battery

Modified carboxymethyl cellulose and grafted acrylic acid, acrylate and styrene to prepare modified cellulose, which solved the problems of low preparation efficiency and poor kinetic performance of lithium-ion battery negative electrode slurry, and achieved more efficient preparation and better kinetic performance.

CN119638896APending Publication Date: 2025-03-18ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411813742.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the production efficiency of the negative electrode slurry of lithium-ion batteries is low and the kinetic performance is poor, mainly due to the difficulty of dispersion of CMC and the lack of conductivity of lithium ions.

Method used

Modified cellulose is prepared by modifying carboxymethyl cellulose and grafting acrylic acid, acrylate and styrene. The modified cellulose is easy to stretch in water and dissolves rapidly, improving the preparation efficiency of the negative electrode slurry, and improving the kinetic performance of lithium-ion batteries by enhancing viscosity and electrolyte properties.

Benefits of technology

Modified cellulose significantly improves the preparation efficiency of the negative electrode slurry, reduces the use of auxiliary materials, increases the energy density of the battery, and improves the kinetic performance of low-temperature discharge of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638896A_ABST
    Figure CN119638896A_ABST
Patent Text Reader

Abstract

The invention discloses modified cellulose. The structural formula of the modified cellulose is as shown in formula (I): # imgabs0 # M is H, Li, Na or K; r1 is an alkyl group or an alkyl acyloxy group of C2-15; r < 2 >, R < 3 > and R < 4 > are independently selected from H, C1-3 alkyl groups or C1-5 alkylacyloxy groups. The grafted acrylic acid, acrylate and styrene chain segments of the modified cellulose disclosed by the invention are easy to stretch in water and quick to dissolve, and can shorten the glue solution preparation time and improve the dynamic performance of lithium ions as a lithium ion battery material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to modified cellulose and a preparation method thereof, a negative electrode material and a lithium ion battery. Background Art

[0002] CMC (carboxymethyl cellulose) is often used as a dispersant for negative electrode slurry of lithium-ion batteries. In the negative electrode slurry of batteries, CMC is adsorbed and coated on the surface of hydrophobic particles such as graphite and conductive agent, so that the graphite particles are evenly dispersed and suspended in the aqueous solution, playing a role of dispersion and stabilization.

[0003] However, since CMC itself is difficult to disperse, it often needs 7-10 hours of dispersing before use, and the production efficiency of negative electrode slurry is low; at the same time, CMC has no lithium ion conductivity, and its coating on the graphite surface as a dispersant will hinder the transmission and diffusion of lithium ions, ultimately leading to the deterioration of the kinetic performance of lithium-ion batteries. Therefore, it is necessary to develop a cellulose that is more efficient in preparing negative electrode slurry and is beneficial to the kinetic performance of batteries. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides modified cellulose and a preparation method thereof, a negative electrode material and a lithium ion battery, aiming to solve the problems of low efficiency in preparing negative electrode slurry and poor battery kinetic performance.

[0005] In order to achieve the above-mentioned object, the present invention provides a modified cellulose, which is prepared by modifying carboxymethyl cellulose with acrylic acid, acrylic ester and styrene, wherein, in parts by weight, the carboxymethyl cellulose is 90 to 110 parts, the acrylic acid is 35 to 40 parts, the acrylic ester is 15 to 18 parts, and the styrene is 2 to 5 parts.

[0006] In some embodiments, the acrylate includes at least one of n-butyl acrylate, n-propyl acrylate, and dodecyl methacrylate.

[0007] In some embodiments, the structural formula of the modified cellulose is as shown in formula (I):

[0008]

[0009] M is H, Li, Na or K; R1 is C 2-15 alkyl or alkanoyloxy; R2, R3, R4 are H, C 1-3 Alkyl or C 1-5 of an alkanoyloxy group.

[0010] In some embodiments, n1=500-1200; and / or, n2=155-360; and / or, n3=50-135.

[0011] In some embodiments, the ratio of m1, m2, and m3 is (10-20): (2-5): (1-2).

[0012] In order to achieve the above object, the present invention also provides a method for preparing the above modified cellulose, comprising the following steps:

[0013] adding a RAFT agent to a cellulose solution for the first time, and then adding an acrylic acid monomer to react under an inert atmosphere to obtain a cellulose-grafted acrylic acid copolymer;

[0014] Adding a RAFT agent to the cellulose grafted acrylic acid copolymer for a second time, and adding an acrylic acid ester monomer to react under an inert atmosphere to obtain a cellulose grafted acrylic acid ester copolymer;

[0015] A RAFT agent is added to the cellulose grafted acrylic acid and acrylate copolymer for the third time, and a styrene monomer is added under an inert atmosphere for reaction, and the cellulose is washed and dried to obtain modified cellulose.

[0016] In some embodiments, the RAFT agent has the general formula: Wherein, R is acetyl or isopropanoyl; Z is C 4-12 of alkylthio, alkyl or phenyl.

[0017] In order to achieve the above object, the present invention also provides a negative electrode material, comprising the above modified cellulose.

[0018] In some embodiments, the negative electrode material includes at least one of a carbon material, a silicon material, an alloy material, and modified cellulose and a binder SBR.

[0019] In order to achieve the above object, the present invention further provides a lithium-ion battery, wherein the battery comprises the above negative electrode material, and the battery comprises any one of a battery cell, a battery module, and a battery pack.

[0020] Beneficial effects of the present invention:

[0021] The modified cellulose provided by the present invention is easy to stretch in water due to the chain segments grafted with acrylic acid, acrylate, and styrene, so that the modified cellulose dissolves quickly, and the preparation time of the glue solution used to prepare the negative electrode slurry is greatly shortened, thereby improving the preparation efficiency of the negative electrode slurry. In addition, the viscosity of the polymer increases after carboxylic acid modification, and the same dispersion and suspension performance can be guaranteed with less dosage. The amount of auxiliary materials used can be reduced, and the energy density of the battery can be improved. At the same time, since the grafted acrylate and styrene functional groups have affinity for the electrolyte, when the modified cellulose is coated on the graphite surface, it is beneficial to the transmission of lithium ions, thereby improving the kinetic performance of the low-temperature discharge of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a characterization result diagram of modified cellulose according to an embodiment of the present invention.

[0023] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0024] In order to make the technical solutions and advantages of the present invention clearer, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods. The drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recorded in the claims.

[0025] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0026] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0027] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0028] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0029] In order to facilitate the understanding of the present invention, the following professional terms are explained:

[0030] RAFT (Reversible Addition-Fragmentation Chain Transfer) reagent is a type of chain transfer reagent used in free radical polymerization reactions, which can achieve precise control of polymer molecular weight and precise design of polymer structure.

[0031] SBR, styrene butadiene latex binder.

[0032] PVDF, polyvinylidene fluoride.

[0033] NMP, N-methylpyrrolidone.

[0034] EC, ethylene carbonate.

[0035] EMC, ethyl methyl carbonate.

[0036] PC, propylene carbonate.

[0037] CMC, carboxymethyl cellulose.

[0038] CMC is often used as a dispersant for negative electrode slurry of lithium-ion batteries. Since CMC itself is difficult to disperse, it often needs to be dispersed for 7-10 hours before use, and the production efficiency of negative electrode slurry is low; at the same time, CMC has no lithium ion conductivity, and its coating on the graphite surface as a dispersant will hinder the transmission and diffusion of lithium ions, and ultimately lead to the deterioration of the kinetic performance of lithium-ion batteries. Therefore, it is necessary to develop a cellulose that is more efficient in preparing negative electrode slurry and is beneficial to the kinetic performance of batteries.

[0039] In view of this, the present invention proposes a modified cellulose, which is prepared by modifying carboxymethyl cellulose with acrylic acid, acrylic ester and styrene. In parts by weight, the carboxymethyl cellulose is 90 to 110 parts, the acrylic acid is 35 to 40 parts, the acrylic ester is 15 to 18 parts, and the styrene is 2 to 5 parts.

[0040] In this scheme, acrylic acid, acrylic acid ester, and styrene are used to modify cellulose and grafted at different main chain sites. The carboxylic acid in acrylic acid ionizes into carboxylate groups, which increases the solubility of cellulose and improves the bonding strength of the electrode by utilizing the strong electronegativity of the carboxyl group; the ester group in the acrylic acid ester increases the affinity of cellulose for the electrolyte and improves the dynamics of the battery cell; styrene is a hydrophobic monomer that adjusts the polarity and takes into account the affinity between the negative electrode material prepared by the modified cellulose and the electrolyte.

[0041] The modified chain segments are easy to stretch in water and dissolve quickly, so the preparation time of the glue used to prepare the negative electrode slurry is greatly shortened, which improves the preparation efficiency of the negative electrode slurry. In addition, the viscosity of the polymer after carboxylic acid modification increases, and the same dispersion and suspension performance can be guaranteed with less dosage. The amount of auxiliary materials used can be reduced and the energy density of the battery can be improved. At the same time, since the grafted acrylate and styrene functional groups have affinity for the electrolyte, when the modified cellulose is coated on the graphite surface, it is conducive to lithium ion transmission, thereby improving the kinetic performance of lithium-ion batteries at low temperature discharge.

[0042] In some embodiments, the acrylate includes at least one of n-butyl acrylate, n-propyl acrylate, and dodecyl methacrylate. The ester group in the acrylate can improve the affinity between CMC and the electrolyte, thereby facilitating the migration of lithium ions and improving the electrochemical performance of the battery; through modification, the desolvation energy barrier of lithium ions in the electrolyte can be reduced, and a solid electrolyte interface film with low interface impedance can be generated, thereby improving the transmission rate of lithium ions and the charge and discharge performance of the battery.

[0043] In some embodiments, the structural formula of the modified cellulose is as shown in formula (I):

[0044]

[0045] M is H, Li, Na or K; R1 is C 2-15 alkyl or alkanoyloxy; R2, R3, R4 are H, C 1-3 Alkyl or C 1-5 of an alkanoyloxy group.

[0046] Acrylic acid, acrylate and styrene are grafted onto cellulose by RAFT reversible addition-fragmentation chain transfer polymerization, and the polymerization degree of each monomer is controllable.

[0047] In some embodiments, n1=500-1200; and / or, n2=155-360; and / or, n3=50-135.

[0048] In formula (I), n1 represents the degree of polymerization of acrylic acid, n2 represents the degree of polymerization of acrylate, and n3 represents the degree of polymerization of styrene. During preparation, the degree of polymerization is controlled by the amount of monomer added during the reaction. The degree of polymerization is an important indicator for measuring the size of polymer molecules, which refers to the average value of the number of repeating units contained in the polymer macromolecular chain. Different degrees of polymerization will affect the viscosity, stability, mechanical properties, heat resistance, compatibility with other materials, etc. of the modified CMC. When used to prepare electrode slurry for lithium-ion batteries, the rheological properties and electrochemical properties of the slurry can be optimized by controlling the degree of polymerization.

[0049] In some embodiments, the ratio of m1, m2, and m3 is (10-20):(2-5):(1-2).

[0050] In formula (I), the modified cellulose polymer includes three monomers modified by acrylic acid, acrylic acid ester and styrene, which are represented by m1, m2 and m3 respectively. The unmodified cellulose monomer not shown in formula (I) is represented by m 未改性 In some embodiments, m1:m2:m3:m 未改性 =(10-20):(2-5):(1-2):(1-5). The appropriate ratio of acid, ester and benzene monomers can obtain moderate viscosity, fast dissolution rate and proper absorption of electrolyte. Too much acid will result in high viscosity and difficult to control viscosity; too much ester and styrene will make the product difficult to dissolve in water and affect the dissolution rate.

[0051] In order to solve the above problems, the present invention also provides a method for preparing the above modified cellulose, comprising the following steps:

[0052] S1: adding a RAFT agent to the cellulose solution for the first time, and adding an acrylic acid monomer to react under an inert atmosphere to obtain a cellulose grafted acrylic acid copolymer;

[0053] S2: adding a RAFT agent to the cellulose grafted acrylic acid copolymer for a second time, and adding an acrylic acid ester monomer to react under an inert atmosphere to obtain a cellulose grafted acrylic acid and acrylic acid ester copolymer;

[0054] S3: adding RAFT agent to the cellulose grafted acrylic acid and acrylate copolymer for the third time, adding styrene monomer to react under an inert atmosphere, washing and drying to obtain modified cellulose. The last step in the preparation of modified cellulose is drying into powder, which is then dissolved in water for use when preparing the negative electrode glue.

[0055] In some embodiments, based on weight parts, the carboxymethyl cellulose is 90 to 110 parts, the solvent is 230 to 270 parts, the acrylic acid is 35 to 40 parts, the acrylic acid ester is 15 to 18 parts, and the styrene is 2 to 5 parts.

[0056] In some embodiments, N,N-dimethylacetamide is used as a solvent to dissolve cellulose, and the cellulose solution is obtained by heating under reflux at 140° C. to dissolve the cellulose.

[0057] In some embodiments, each addition of the RAFT agent is followed by stirring at 70° C. for 30 min.

[0058] In some embodiments, the inert atmosphere is a gas that does not cause side reactions to replace the air in the reactor, and the gas includes nitrogen, rare gases, and the like.

[0059] In some embodiments, the addition of acrylic acid, acrylate, and styrene monomers in steps S1, S2, and S3 is done by dropwise addition, the reaction temperature is 70°C to 85°C, and the reaction time is no less than 9 hours.

[0060] In some embodiments, the RAFT agent has the general formula: Wherein, R is acetyl or isopropanoyl; Z is C 4-12 The RAFT agent is selected depending on the type of monomer used. Dithioester RAFT agents are suitable for the polymerization of highly active monomers. In some embodiments, the RAFT agent is 2-(dodecylthiothiocarbonylthio)-methylpropionic acid, which can more effectively control the modified polymerization reaction and reduce the generation of side reactions.

[0061] In order to solve the above problems, the present invention also provides a negative electrode material, including the above modified cellulose. The negative electrode material is used to coat the surface of the negative electrode current collector to prepare a negative electrode sheet, the modified cellulose is used as a dispersant, and the negative electrode material also includes at least a conductive material and a binder.

[0062] In some embodiments, the negative electrode material includes at least one of a carbon material, a silicon material, an alloy material, and modified cellulose and a binder SBR. The carbon material includes a graphite material and an amorphous carbon, and the alloy material includes an alloy of a metal and a semi-metal. In some embodiments, the negative electrode material includes graphite, modified cellulose, and a binder SBR in a mass ratio of 97:1.5:1.5. When expressing the formula ratio, the amount of pure modified cellulose is used instead of the amount of glue.

[0063] In order to solve the above problems, the present invention also proposes a lithium-ion battery, which includes the above-mentioned negative electrode material, which is a slurry, arranged on the surface of the negative electrode collector, and prepared into a negative electrode sheet through processes such as baking, rolling, striping, and welding of pole ears. The battery includes any one of a battery cell, a battery module, and a battery pack.

[0064] Example 1

[0065] 1. Preparation of modified cellulose

[0066] The raw materials used in the following process for preparing modified cellulose are calculated by weight.

[0067] 100 parts of cellulose were added to 250 parts of N,N-dimethylacetamide solvent, and the cellulose was refluxed and dissolved at 140°C to obtain a cellulose solution. 4 parts of 2-(dodecylthiothiocarbonylthio)-methylpropionic acid RAFT reagent were added to the cellulose solution, and the mixed solution was stirred at 70°C for 30 minutes to react the cellulose with the RAFT reagent to obtain a first mixed solution, and the reaction container was replaced with inert gas for 30 minutes. 35 parts of acrylic acid monomer were added dropwise to the first mixed solution under an inert gas atmosphere at 70°C for 18 hours to obtain a cellulose grafted acrylic acid copolymer.

[0068] The cellulose grafted acrylic acid copolymer was heated to reflux at 140°C, and then 2.2 parts of RAFT agent were added, and the mixture was reacted at 80°C with stirring for 30 minutes. Then, 15 parts of n-butyl acrylate monomer were added dropwise under an inert gas atmosphere at 70°C and reacted for 12 hours to obtain a cellulose grafted acrylic acid and acrylic acid ester copolymer.

[0069] The cellulose grafted acrylic acid and acrylate copolymer is heated to reflux at 140°C, and then 3.5 parts of RAFT agent are added, and the reaction is carried out at 85°C with stirring for 30 minutes. Then, 5 parts of styrene monomer are added dropwise under an inert gas atmosphere at 70°C to react for 9 hours. Finally, the product is washed and filtered with acetone, and dried at 60°C to obtain a cellulose grafted acrylic acid-acrylate-styrene copolymer, which is the target product modified cellulose.

[0070] 2. Preparation of lithium-ion batteries

[0071] 1. Graphite, dispersant: modified cellulose, binder SBR, in a mass ratio of 97:1.5:1.5, are fully stirred and dispersed to obtain negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode current collector. The current collector coated with the negative electrode slurry is prepared into a negative electrode sheet through baking, rolling, striping, welding of the pole ear and other processes. Among them, SBR is purchased from TRD104A of JSR Company.

[0072] 2. Add NMP to the active material lithium cobalt oxide, conductive carbon black, and binder PVDF in a mass ratio of 96:2:2, stir and mix thoroughly to obtain a positive electrode slurry, evenly coat it on the positive electrode current collector aluminum foil, and prepare it into a positive electrode sheet through processes such as baking, rolling, slitting, and welding the pole ears.

[0073] 3. Assemble the above-mentioned positive electrode sheet, negative electrode sheet, separator and aluminum-plastic film, inject electrolyte after baking, and obtain a lithium-ion battery through processes such as standing, forming, secondary sealing and testing.

[0074] Embodiment 2-6

[0075] In Examples 2-6, except that the types and weight ratios of the monomers used to prepare the modified cellulose were added as shown in Table 1, everything else was the same as in Example 1.

[0076] Table 1. Monomer types and weight parts of Examples 1-6

[0077]

[0078] Comparative Example 1:

[0079] 1. Preparation of negative electrode sheet: Graphite, dispersant CMC, and binder SBR are fully stirred and dispersed in a mass ratio of 97:1.5:1.5 to obtain negative electrode slurry. The negative electrode slurry is coated on the negative electrode current collector, and the negative electrode current collector coated with the negative electrode slurry is prepared into a negative electrode sheet through baking, rolling, striping, and welding of the pole ears. Among them, the dispersant CMC was purchased from Daicel's CMC2200; SBR was purchased from JSR's TRD104A.

[0080] 2. Prepare positive electrode sheets: Add active material lithium cobalt oxide, conductive carbon black, and binder PVDF in a mass ratio of 96:2:2 with NMP, stir and mix thoroughly to obtain positive electrode slurry, evenly coat it on the positive electrode collector aluminum foil, and prepare it into positive electrode sheets through processes such as baking, rolling, slitting, and welding of pole ears.

[0081] 3. Assemble the above-mentioned positive electrode sheet, negative electrode sheet, separator and aluminum-plastic film, inject electrolyte after baking, and obtain a lithium-ion battery through processes such as standing, forming, secondary sealing and testing.

[0082] Comparative Example 2:

[0083] Except that the types and weight proportions of the monomers used to prepare the modified cellulose are 30 parts of acrylic acid, 15 parts of n-butyl acrylate and 10 parts of styrene, everything else is the same as in Example 1.

[0084] Comparative Example 3:

[0085] Except that the types and weight proportions of the monomers used to prepare the modified cellulose are 25 parts of acrylic acid, 20 parts of n-butyl acrylate and 10 parts of styrene, everything else is the same as in Example 1.

[0086] Performance Testing

[0087] The modified celluloses prepared in Examples 1-6 and Comparative Examples 2-3, and the cellulose dispersant used in Comparative Example 1 were subjected to relevant performance tests.

[0088] 1. Infrared test of Example 1

[0089] See also Figure 1 Infrared spectrum, 3400cm -1 Corresponding to the stretching vibration peaks of cellulose OH, 2952, 2856 cm -1 The corresponding CH2-asymmetric and CH symmetric stretching vibration peaks on the side chain are 1728 cm -1 Corresponding to C=O stretching vibration absorption peaks, 1492, 1451 cm -1 Corresponding to the characteristic absorption peak of benzene ring, 2110cm -1 There are no peaks on the left and right, indicating that the N3 reaction of cellulose azido is complete.

[0090] 2. Electrolyte solvent swelling test

[0091] The modified cellulose prepared in Examples 1-6 and Comparative Examples 2-3, and the dispersant CMC used in Comparative Example 1, were mixed with water at a ratio of 1.5:98.5, and after being fully stirred, a glue solution was prepared, which was poured into a mold and dried at 80°C for 8 hours to obtain a glue film. The glue film was placed in a solvent of EC:EMC:PC=1:1:1, and baked at 45°C for 72 hours. The complete dissolution time, glue viscosity, and glue absorption rate of the glue film were tested, wherein the glue viscosity test adopted the conventional test method of the national standard, which is not described in detail here. The test results are shown in Table 2.

[0092] Table 2. Electrolyte solvent swelling test results

[0093] Examples Complete dissolution time / h Glue viscosity / mPa·s Film liquid absorption rate Example 1 2.8 6137 2.5% Example 2 2.8 5119 2.3% Example 3 2.4 5210 2.3% Example 4 2.9 4932 2.9% Example 5 3.1 7711 2.5% Example 6 3.2 4546 2.5% Comparative Example 1 8.8 5463 0.2% Comparative Example 2 5.2 3416 2.3% Comparative Example 3 5.6 3525 4.7%

[0094] From the data in Table 2, it can be seen that the time required for the complete dissolution of the adhesive film prepared in Examples 1-6 is 2.4 to 3.2 hours, while the time required for Comparative Example 1 is 8.8 hours. That is, the modified cellulose provided by the present invention greatly improves the production speed of the adhesive solution and reduces the number of adhesive making equipment used compared to the commonly used dispersant CMC (carboxymethyl cellulose) in the prior art. The adhesive film prepared in Comparative Example 1 basically does not absorb liquid, and the liquid absorption rate of the modified cellulose film prepared in Examples 1-6 is between 2.3% and 2.9%. This modified cellulose has good affinity for the electrolyte as a dispersant. Due to the small amount of acid added in Comparative Examples 1 to 2, the complete dissolution speed is significantly slower than that of Examples 1 to 6, and the viscosity of the adhesive solution is also low.

[0095] 3. Negative electrode slurry test

[0096] The negative electrode slurries prepared in Examples 1-6 and Comparative Example 1 were tested for slurry discharge viscosity, slurry viscosity after standing for 24 hours, and electrode sheet adhesion, and the test results are shown in Table 3. The slurry discharge viscosity and the viscosity after standing for 24 hours were tested using conventional test methods of national standards, which are not described in detail here.

[0097] Pole piece adhesion test: The negative electrode prepared by the above corresponding embodiment is cut into strips with a width of 20 mm and a length of 150 mm. Prepare a glass plate with a clean, dust-free and uneven surface, and stick a 3M scotch double-sided tape with a width of 24 mm on the glass plate. Stick one end of the long strip of pole piece on the double-sided tape with a length of 80 mm, and roll it repeatedly with a roller to make the pole piece fit tightly with the glass plate. Use an electronic universal testing machine to perform a pole piece peeling test to measure the pole piece adhesion. Make one end of the pole piece fixed on the glass plate face up, and the other end of the glass plate is fixed with a lower clamp. The free end of the pole piece is folded upward 180° and fixed with an upper clamp. At room temperature, keep the lower clamp stationary, and stretch the upper clamp upward at a tensile rate of 80 mm / min. Take the average peeling force of the 20mm-80mm segment as the adhesion obtained by a single group test, in N / m. Each group of experiments was measured 5 times in parallel according to the above method, and the average value was taken after removing the data with significant differences.

[0098] Table 3. Negative electrode slurry test results

[0099]

[0100] From the data in Table 3, it can be seen that the slurries prepared in Examples 1 to 6 and Comparative Example 1 all rose slightly after standing for 24 hours, which is a normal phenomenon. The electrode bonding force of Examples 1-6 is much higher than that of Comparative Example 1; this is because the carboxyl and acrylate single chains grafted on the modified cellulose prepared in Examples 1-6 can effectively combine with the binder SBR to improve the bonding effect of the binder SBR. Comparative Examples 1 to 2 have a low acid content, low and unstable slurry viscosity, a high viscosity increase, and a low electrode bonding force.

[0101] 4. Performance test of lithium-ion batteries

[0102] The lithium ion batteries prepared in the above Examples 1-6 and Comparative Example 1 were subjected to low temperature discharge tests, and the test results are shown in Table 4. The lithium ion battery design capacity is 5000mAh, the discharge range is 3V-4.45V, the discharge is 0.2C, the discharge capacity at 25°C is used as the reference capacity, and the battery is charged to a full charge of 4.45V at 25°C, and the discharge tests are performed at 0°C, -10°C, and -20°C, respectively. The test results are shown in Table 4.

[0103] Table 4. Battery performance test results

[0104] Examples 25℃ 0℃ -10℃ -20℃ Example 1 100.0% 89.9% 82.6% 74.5% Example 2 100.0% 89.5% 82.4% 73.9% Example 3 100.0% 88.8% 82.0% 74.7% Example 4 100.0% 89.7% 82.7% 74.2% Example 5 100.0% 88.8% 82.2% 73.8% Example 6 100.0% 88.3% 81.4% 73.5% Comparative Example 1 100.0% 85.9% 77.6% 65.2% Comparative Example 2 100.0% 86.2% 76.4% 64.8% Comparative Example 3 100.0% 86.5% 75.6% 63.5%

[0105] It can be seen from the data in Table 4 that the low-temperature discharge capacity of the lithium-ion batteries prepared in Examples 1-6 is significantly higher than that of the lithium-ion battery prepared in Comparative Example 1, which indicates that the modified cellulose provided by the present invention as a dispersant for the negative electrode slurry can significantly improve the kinetic performance of the lithium-ion battery.

[0106] In summary, the modified cellulose provided by the present invention dissolves quickly because the chain segments of grafted acrylic acid, acrylate, and styrene are easily stretched in water, and the time for preparing the glue is shorter than that of conventional CMC. At the same time, because the modified cellulose has carboxylic acid functional groups, its viscosity is better than that of conventional CMC, and its dosage is less while ensuring the same dispersion and suspension properties. At the same time, because the grafted acrylate and styrene functional groups have affinity for the electrolyte, when the modified cellulose is coated on the graphite surface, it is beneficial to the transmission of lithium ions, thereby improving the dynamic properties of lithium ion batteries such as low-temperature discharge.

[0107] Those skilled in the art may combine and associate different embodiments or examples and features of different embodiments or examples described in this specification without mutual contradiction.

[0108] The above description is only a partial or preferred embodiment of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.

Claims

1. A modified cellulose, characterized in that: The structural formula of the modified cellulose is shown in formula (I): M is H, Li, Na or K; R1 is C 2-15 An alkyl or alkanoyloxy group; R2, R3, R4 are independently selected from H, C 1-3 Alkyl or C 1-5 of an alkanoyloxy group.

2. The modified cellulose according to claim 1, characterized in that The modified cellulose is prepared by modifying carboxymethyl cellulose with acrylic acid, acrylic acid ester and styrene. In parts by weight, the carboxymethyl cellulose is 90-110 parts, the acrylic acid is 35-40 parts, the acrylic acid is 15-18 parts, and the styrene is 2-5 parts.

3. The modified cellulose according to claim 1, characterized in that The acrylic acid ester includes at least one of n-butyl acrylate, n-propyl acrylate and dodecyl methacrylate.

4. The modified cellulose according to claim 1, characterized in that n1=500~1200; and / or, n2=155-360; And / or, n3=50~135.

5. The modified cellulose according to claim 1, characterized in that The ratio of m1, m2 and m3 is (10~20):(2~5):(1~2).

6. A method for preparing modified cellulose according to any one of claims 1 to 5, characterized in that: The steps include: adding a RAFT agent to a cellulose solution for the first time, and then adding an acrylic acid monomer to react under an inert atmosphere to obtain a cellulose-grafted acrylic acid copolymer; Adding a RAFT agent to the cellulose grafted acrylic acid copolymer for a second time, and adding an acrylic acid ester monomer to react under an inert atmosphere to obtain a cellulose grafted acrylic acid ester copolymer; A RAFT agent is added to the cellulose grafted acrylic acid and acrylate copolymer for the third time, and a styrene monomer is added under an inert atmosphere for reaction, and the cellulose is washed and dried to obtain modified cellulose.

7. The method for preparing modified cellulose according to claim 6, characterized in that: The general formula of the RAFT agent is: Wherein, R is acetyl or isopropanoyl; Z is C 4-12 of alkylthio, alkyl or phenyl.

8. A negative electrode material, characterized in that The negative electrode material comprises the modified cellulose according to any one of claims 1 to 5.

9. The negative electrode material according to claim 8, characterized in that The negative electrode material includes at least one of a carbon material, a silicon material, and an alloy material, as well as modified cellulose and a binder SBR.

10. A lithium ion battery, characterized in that: The battery comprises the negative electrode material as claimed in claim 8 or 9, and the battery comprises any one of a battery cell, a battery module, and a battery pack.

Citation Information

Patent Citations

  • Adhesive for lithium ion battery

    CN105504169A

  • Adhesive for lithium ion battery as well as preparation method and application of adhesive

    CN115911391A